GREEN MARKETING: STRENGTHEN THE BRAND IMAGE AND INCREASE THE CONSUMERS’ PURCHASE DECISION - Genoveva Genoveva; Dian Ridho Samukti (Universitas Mercu Buana, 2020)
This study aims to determine how much influence green marketing toward consumers’ purchase decision mediated by brand image of Ades mineral water in Jabodetabek. The type of research used in this study is descriptive with a quantitative approach. The variables in this study are green marketing, brand image and purchase decision. The population in this study is consumers who have bought and consumed Ades mineral water. This study uses 268 people as samples selected by non-probability sampling method. This study uses Descriptive and Structural Equation Modeling analysis to analyze data with the help of SPSS and AMOS software. The results of this study indicate that 1) green marketing directly has a significant influence toward brand image of Ades mineral water, 2) green marketing directly has a significant influence toward purchase decision of Ades mineral water, 3) brand image directly has a significant influence toward purchase decision of Ades mineral water, and 4) green marketing indirectly has a significant influence toward purchase decision of Ades mineral water through brand image as a mediating variable.